KEMAMPUAN BACA AL-QUR'AN SIS WIKELASIIPADA TIGA SMP DIKABUPATEN ENREKANG - Badruzzaman Badruzzaman (Al-Qalam, 2007)
This research was conducted in Enrekang, South Sulawesi. Especiallyat SMPN 1 Enrekang, SMPN 3 Enrekang, and SMP Darul Falah. Thisresearch aims to describe the student ability on reading Al-Qur'an andfactors influence that ability. This uses quantitative method, where datawas collected by questioner. Then, data was analyzed by statisticalanalysis.This research indicates that ability degree on reading Al-Qur'an ofthose students of the three schools is commonly good enough. Theirmean score are 78.6 to 95.5. SMP Darul Falah get the highest score(95.5), SMPN 1 Enrekang get middle score (87.7), and SMPN 3Enrekang get the lowest score (78.6). This good ability was influencedby some factors, are method in reading Al-Qur'an and the motivationof students.